Removal of Cr 3+ by electrocoagulation from simulated wastewater - Ulambayar, R; Oyuntsetseg, J; Tsiiregzen, A; Bayaraa, D (Mongolian Journal of Chemistry, 2014)
Trivalent chromium (Cr3+) removal from aqueous solution by electrocoagulation using iron electrodes material was investigated in this paper. Effects of current density, initial concentration of Cr 3+, operating time, pH, electrode distance, and operating cost have been investigated. At higher current density and solution pH, remarkable removal of Cr3+ was observed. Experiments have been show that the maximum removal percentage of the Cr3+ 99.89 % was at initial concentration 1000mg/L, current density 9.34mA/cm2 and reaction time 1 hours. Energy consumption was calculated for Cr3+ removal at different time. The method is observed to be very effective in the removal Cr3+ ion from aqueous solution. Electrocoagulation process need simple equipment, designable any size, use any chemical substances and low operating cost. DOI: http://doi.dx.org/10.5564/mjc.v15i0.330 Mongolian Journal of Chemistry 15 (41), 2014, p89-93